Back in business - Binkow, Bruce; McAlevey, Pete (Kuala Lumpur : Speedy Video Distributors [distributor])
Joe Elkhart, an ex-cop discharged from the force and ostracized by his fellow officers for attempting to expose a corrupt senior officer, Emery Ryker. Now making a living as a mechanic, Joe's trying to survive life after his divorce with the help of a radio talk show therapist. Tony Dunbar, Joe's ex-partner who's recently started working undercover with the FBI to try and bring down multi-millionaire drug dealer David Ashby. When Joe visits Tony after a long absence, sparks - as well as bullets - fly, and Joe finds himself once again in the middle of the reigning chaos.
Writers, Brad Fuller & Rick Natkin
VCD format
Keywords: Violance in motion picture; Drugs in motion pictures